Bordetella pseudohinzii targets cilia and impairs tracheal cilia-driven transport in naturally acquired infection in mice - Perniss, Alexander; Schmidt, Nadine; Gurtner, Corinne; Dietert, Kristina; Schwengers, Oliver; Weigel, Markus; Hempe, Julia; Ewers, Christa; Pfeil, Uwe; Gärtner, Ulrich; Gruber, Achim D.; Hain, Torsten; et al. (My University, 2018)
Several species of the Gram-negative genus Bordetella are the cause of respiratory infections in mammals and birds, including whooping cough (pertussis) in humans. Very recently, a novel atypical species, Bordetella pseudohinzii, was isolated from laboratory mice. These mice presented no obvious clinical symptoms but elevated numbers of neutrophils in bronchoalveolar lavage fluid and inflammatory signs in histopathology. We noted that this species can occur at high prevalence in a mouse facility despite regular pathogen testing according to the FELASA-recommendations. Affected C57BL/6 J mice had, in addition to the reported pulmonary alterations, tracheal inflammation with reduced numbers of ciliated cells, slower ciliary beat frequency, and largely (>50%) compromised cilia-driven particle transport speed on the mucosal surface, a primary innate defence mechanism. In an in vitro-model, Bordetella pseudohinzii attached to respiratory kinocilia, impaired ciliary function within 4 h and caused epithelial damage within 24 h. Regular testing for this ciliotropic Bordetella species and excluding it from colonies that provide mice for lung research shall be recommended. On the other hand, controlled colonization and infection with Bordetella pseudohinzii may serve as an experimental model to investigate mechanisms of mucociliary clearance and microbial strategies to escape from this primary innate defence response.
Keywords: ddc:610